2019
DOI: 10.3389/fmed.2019.00274
|View full text |Cite
|
Sign up to set email alerts
|

Skin Imaging Using Ultrasound Imaging, Optical Coherence Tomography, Confocal Microscopy, and Two-Photon Microscopy in Cutaneous Oncology

Abstract: With the recognition of dermoscopy as a new medical technology and its available fee assessment in Korea comes an increased interest in imaging-based dermatological diagnosis. For the dermatologist, who treats benign tumors and malignant skin cancers, imaging-based evaluations can assist with determining the surgical method and future follow-up plans. The identification of the tumor's location and the existence of blood vessels can guide safe treatment and enable the use of minimal incisions. The recent develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 47 publications
0
29
0
2
Order By: Relevance
“…With the fast-growing ultrasound transducer technology, numerous computational methods have also been studied to further improve the performance of transducers by reducing noise in the transducer signal [ 198 , 199 ]; the result has been higher quality images [ 5 , 200 , 201 ]. With the advancement of ultrasound technology, more biomedical applications, which are currently performed using optical technologies, can be realized [ 12 , 202 , 203 , 204 , 205 , 206 , 207 , 208 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the fast-growing ultrasound transducer technology, numerous computational methods have also been studied to further improve the performance of transducers by reducing noise in the transducer signal [ 198 , 199 ]; the result has been higher quality images [ 5 , 200 , 201 ]. With the advancement of ultrasound technology, more biomedical applications, which are currently performed using optical technologies, can be realized [ 12 , 202 , 203 , 204 , 205 , 206 , 207 , 208 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, many novel noninvasive biomedical imaging modalities, such as magnetic resonance imaging (MRI), ultrasonography, reflectance confocal microscopy (RCM), and optical coherence tomography (OCT) have been utilized in both clinical and research settings to aid in the diagnosis of skin cancer, permitting real-time visualization of internal structures and their functions (e.g. vascular network, flow rate, and elasticity) in the skin [3][4][5][6][7]. They also offer the advantage and convenient ability of performing repeated imaging of the same lesions without harmful adverse effects, enabling the observation of dynamic and long-term changes over time.…”
Section: Introductionmentioning
confidence: 99%
“…A skin ultrasound is noteworthy as a noninvasive alternative to rapid and noninvasive quantification of skin tissue 12 . Various studies have shown significant progress in the use of high‐frequency ultrasonic molding, diagnosis, and determination of the treatment effect on the skin‐related condition 13,14 . The first skin ultrasound was used to measure skin repair procedures, for example, in systemic scleroderma.…”
Section: Introductionmentioning
confidence: 99%